Variasi Bahasa Dayak Kabupaten Landak Dialek Ahe pada Mahasiswa PGRI Pontianak - Apria; Gusti Yani; Kumala Dewi; Ria; Fitri Wulansari (CV. Alfa Pustaka, 2026)
This study aims to describe the language variation of the Ahe dialect of the Dayak language among students of Universitas PGRI Pontianak from Landak Regency. The research employed a qualitative descriptive approach within a sociolinguistic framework. Data were collected through observation, interviews, and documentation involving students who are native speakers of the Ahe dialect. Data were analyzed through data reduction, data presentation, and conclusion drawing, while triangulation was used to ensure data validity. The findings indicate that the Ahe dialect is still predominantly used in informal communication among students who share the same regional background. The study also found instances of code-mixing between Indonesian and the Ahe dialect occurring naturally in everyday conversations. Factors influencing the use of the Ahe dialect include regional origin, familiarity, cultural identity, and communication context. In formal situations, students tend to use Indonesian to conform to academic norms. The findings suggest that the Ahe dialect continues to serve as a strong marker of cultural identity and contributes to the maintenance of the regional language within the university environment.